A quantile approach to the relationship between body mass, wealth, and inequality - Scott Alan Carson (Center for Economic Studies and ifo Institute (CESifo), 2010)
Little research exists on the historical relationship between BMI variation, wealth, and inequality. This study finds that 19th century US black and white BMIs were distributed symmetrically; neither wasting nor obesity was common. Nineteenth century BMI values were also greater for blacks than whites. There was a positive relationship between 19th century BMIs and average state-level wealth, and an inverse relationship between BMI and wealth inequality. After controlling for wealth and inequality, rural agricultural farmers had greater BMI values than their urban counterparts in other occupations.
Keywords: I10; N00; 330; BMI; wealth; inequality; race; Körpergewicht; Vermögensverteilung; Weiße; Schwarze; Geschichte; USA